An idea for a new modeling approach of climatic changes. A correlation study for Cyprus - Pittaki, Z.; Orphanides, Antia; Gekas, Vassilis (My University, 2011)
Mathematical Modeling in climatic changes prediction has been based on more or less simple energy balances considering the Earth along with its atmosphere, with the so-called solar "constant" taken as an invariant. However evidence has been supplied in previous WSEAS Conferences that this constant, S, does not remain a constant but it does fluctuate, following the cycles of the solar activity. Furthermore the transmission parameters concerning the input and the output energy, τ V and τ IR from/to the system Earth-Atmosphere also vary and this reflects the human activity leading to increased greenhouse gas quantities, being blamed for a dramatic climatic change the last decades. Thus, considering those fluctuating properties, the following equation for Earth's mean temperature, T, has been developed (A being albedo equal to 0.3 and σ is the Stefan-Boltzmann constant) (Equation presented) with the following multivariate treatment: (Equation presented) We need to obtain the derivatives: (Equation presented) because all S, τ IR, τ V change
Keywords: Solar energy; Climate change; Computer simulation; Greenhouse gases; Innovation; Navigation; Solar radiation